THE INFLUENCE OF LEARNING MEDIA AND LEARNING MOTIVATION ON CRITICAL THINKING ABILITY OF FE UNJ STUDENTS - Musfikhuna, Khosyatillah; Parlyna, Ryna; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of learning media in the form of audio-visual and learning motivation on critical thinking skills. This research was conducted for six months starting from January 2021 to July 2021. The method used in this study is a quantitative method through a surveys by distributing questionnaires to respondents which is carried out online via Google Form. The population in this study were students of the Faculty of Economics, State University of Jakarta, and the samples taken were active students of the Faculty of Economics, State University of Jakarta, class of 2017 and 2018 who had or were using audio-visual learning media. The sampling technique used was purposive sampling as many as 243 respondents. While the analysis technique in this study uses simple linear regression. The results of this study are in accordance with the hypothesis that has been formulated that: There is a positive and significant influence of learning media on critical thinking skills. There is a positive and significant influence between learning motivation on critical thinking skills.